The impact of palliative care in the management of pain and suffering in urgent and emergency situations - Avanci Júnior, José Amarildo; da Silva, Marcelo Fontes; Carine Otilia Vicari Pauperio; Cynthia Prudencio Coelho; Samia Milan Simões; Carmela Mottecy de Oliveira Baltazar (Innovative Journal of Medical and Health Sciences, 2023)
The study aimed to identify best practices, training needs, required resources, and potential cultural resistances, with the goal of integrating palliative care as a fundamental component of emergency medical services, aligning medical treatment with the individual needs and values of patients. A literature review was conducted, searching for articles that referenced or analyzed the impacts of palliative care on pain and suffering management in emergency situations and how healthcare facilities respond to the merging of these two areas. The findings of this article underscored the importance of implementing palliative care in emergency departments to provide more compassionate, efficient, and humanized care to patients in critical conditions. However, there was a noticeable gap in such implementation within health services, given that the integration of palliative care and emergency sectors is still nascent in Brazil, with only a few healthcare units adopting this practice. Nevertheless, the growing demand for health services due to an aging population, the rise in chronic diseases, and the occurrence of complex emergencies highlight the imperative to incorporate palliative care in these settings. As such, it is crucial to promote training and continuing education for healthcare professionals regarding the principles and practices of palliative care, incorporating them into the academic curriculum of medical and health courses, aiming for the establishment of clear public policies and guidelines from governing and regulatory bodies. This includes integrating palliative care into health policies as well as developing protocols and standards to guide the practice of such care in emergency medical services.